Correction: Role of microglia in the dissemination of Zika virus from mother to fetal brain. - Pei Xu; Chao Shan; Tiffany J Dunn; Xuping Xie; Hongjie Xia; Junling Gao; Javier Allende Labastida; Zou Jing; Paula P Villarreal; Caitlin R Schlagal; Yongjia Yu; Gracie Vargas; et al. (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0008413.].